Implementasi Literasi Guna Meningkatkan Kompetensi, Tulis Dan Hitung Siswa Di SDN 066045 Medan Helvetia - Zuhri Fitransyah Hasibuan; Gusti Pirandy (Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Field Work Practicum (PKL) is one of the courses that must be completed by students of USU's Social Welfare Study program under the guidance of trained and qualified supervisors. PKL 1 works closely with the MBKM Teaching Campus Partners-USU activities which require students to go directly to schools that are USU-Partners. The role of the teaching campus is very helpful for teachers in terms of literacy and numeracy to improve students' reading, writing and numeracy competencies at UPT SDN 066045 Medan Helvetia. During the implementation of the teaching campus program there were several problems, namely learning seemed monotonous, rigid and dominated by teachers who did not apply a variety of learning systems. Thus, learning breakthroughs are needed that are able to make students active in reading, writing and even counting. This teaching campus program does not only aim at increasing literacy and numeracy, but this program also aims to help improve the quality of schools in terms of learning, administration, and technology. This assistance is expected to be able to improve the quality of student learning so as to create a safe and comfortable learning environment for students to study. This practicum uses the CaseWork method proposed by Zastrow, as follows: Intake and contract, Assessment, Planning, Intervention, Evaluation, Termination. The results of this practicum activity aim that the children at SDN 066045 Medan Helvetia can understand learning well